Human–Nature Imbalance in Sumatera Ecological Disasters: Mubādalah as a Framework for a Just and Sustainable Ecological Model - Iskandar; Abu Yazid Abu Bakar; Hakis (Journal of Islamic Mubadalah, 2025)
Ecological disasters in Sumatra, including flash floods and landslides, demonstrate a profound imbalance in human–nature relations resulting from upstream watershed degradation and development practices that disregard ecological carrying capacity. This article aims to identify the forms of this imbalance, analyze them through the framework of mubādalah, and propose an applied ecological model that is both just and sustainable for national environmental governance. The novelty of this study lies in extending mubādalah as an ethic of reciprocity beyond interpersonal relations to encompass the human–nature nexus, positioning nature as a relational subject rather than a passive object. Employing a qualitative–analytical approach, the study draws on literature reviews, disaster reports, and Islamic ecological scholarship. The analysis integrates reciprocity-based ecological theory and ecological spatial-planning frameworks. The findings indicate that the failure to cultivate reciprocal relations with nature exacerbates disaster risks and weakens community resilience. Consequently, the study argues for the importance of a reciprocity-oriented ecological paradigm that recognizes nature as a partner in development. Recommendations include strengthening reciprocity-based mitigation policies, advancing upstream landscape rehabilitation, and integrating the ethical principles of mubādalah into environmental governance and education as a response to the increasing frequency of ecological disasters at the national level.